Coupling virtual reality and motion platforms for snowboard training - Hament, B.; Cater, A.; Oh, P. Y. (14th International Conference on Ubiquitous Robots and Ambient Intelligence (URAI), 2017)
An unobtrusive and low-cost landing analysis could not only support sports science research and ski jumping training but also decrease the risk of overuse and injuries. Although ski jumping biomechanics has been extensively researched, there is no known study on an unobtrusive analysis of the landing phase of actual ski jumps. In this work, we propose a landing momentum determination with inertial-magnetic measurement units (IMMUs) attached to the skis. We evaluate the calculated momenta against a mobile force plate and achieve accuracies of more than 90 % for three out of four jumps. Although the robustness of the measurement process can still be improved, our proposed algorithm builds the first step towards an IMMU-based landing analysis in ski jumping.